2022
DOI: 10.1155/2022/3012778
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Paradox of COVID-19 in Neurological Complications with Emphasis on Parkinson’s and Alzheimer’s Disease

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a human coronavirus (HCoV) that has created a pandemic situation worldwide as COVID-19. This virus can invade human cells via angiotensin-converting enzyme 2 (ACE2) receptor-based mechanisms, affecting the human respiratory tract. However, several reports of neurological symptoms suggest a neuroinvasive development of coronavirus. SARS-CoV-2 can damage the brain via several routes, along with direct neural cell infection with the coronavirus. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 140 publications
(170 reference statements)
1
35
0
Order By: Relevance
“…Thirdly, this study was conducted relatively soon after diagnosis, and differences between COVID-19 cases and non-COVID cases may arise after a longer convalescent period, when persistent symptoms of COVID may become more apparent. These findings do not address potential changes in physical and mental status among patients with neurodegenerative disorders such as Parkinson's or Alzheimer's Disease ( Rai et al, 2022 ). We did not evaluate physical activity levels before, during or after illness.…”
Section: Discussionmentioning
confidence: 88%
“…Thirdly, this study was conducted relatively soon after diagnosis, and differences between COVID-19 cases and non-COVID cases may arise after a longer convalescent period, when persistent symptoms of COVID may become more apparent. These findings do not address potential changes in physical and mental status among patients with neurodegenerative disorders such as Parkinson's or Alzheimer's Disease ( Rai et al, 2022 ). We did not evaluate physical activity levels before, during or after illness.…”
Section: Discussionmentioning
confidence: 88%
“…AD is a common age-related neurodegenerative disease characterized by impairment of memory and cognitive function [1][2][3][4][5]. The deposition of amyloid β (Aβ) protein and tau protein is currently considered a neuropathological hallmark of AD [6].…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson’s disease (PD) is known as a common neurodegenerative disease with major clinical manifestations of motor dysfunction, such as cognitive impairment. , PD usually occurs in people with the age of over 65 and is caused by the progressive degeneration of dopaminergic neurons in the substantia nigra (SN). The cause of PD is still elusive. Previous studies have demonstrated that the pathogenesis of PD is related to aging factors, environmental factors, genetic factors, oxidative stress, free radical formation, and associated nerve inflammation, but recent evidence suggests that chronic nerve inflammation caused by microglia activation may be important in the degenerative process. , Activated microglia are a major factor in neuroinflammation and dopaminergic neurodegeneration. , Overactivation of microglia results in the release of several neurotoxic factors, which contributes to the process of dopaminergic neurodegeneration. , Therefore, inhibition of microglial activation may contribute to the treatment and prevention of PD.…”
Section: Introductionmentioning
confidence: 99%